2021
DOI: 10.1213/ane.0000000000005606
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Complications Associated with SARS-CoV-2 in Pediatric Patients

Abstract: BACKGROUND: Coronavirus disease 2019 (COVID-19) is associated with high perioperative morbidity and mortality among adults. The incidence and severity of anesthetic complications in children with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is unknown. We hypothesized that there would be an increased incidence of intra- and postoperative complications in children with SARS-CoV-2 infection as compared to those with negative testing. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
6
28
0
1
Order By: Relevance
“…Moreover, severe morbidity and mortality were absent in both the groups. 19 Our findings are in concurrence with earlier studies in non-neurosurgical population that reported negligible impact of COVID-19 on clinical outcomes.…”
Section: Comparison With Previous Literaturesupporting
confidence: 92%
“…Moreover, severe morbidity and mortality were absent in both the groups. 19 Our findings are in concurrence with earlier studies in non-neurosurgical population that reported negligible impact of COVID-19 on clinical outcomes.…”
Section: Comparison With Previous Literaturesupporting
confidence: 92%
“…Kavanagh et al did not identify any pulmonary complications in infected children who underwent surgery in a two-month time frame 16 . However, Saynhalath et al concluded increased risk for pulmonary complications in infected children in a study which included matched controls 11 . Our present study fortifies Saynhalath's conclusions, helping to clarify the risks and benefits to proceeding with surgery in infected children.…”
Section: Discussionmentioning
confidence: 98%
“…Retrospective studies have found that adult surgical patients with SARS-CoV-2 infection are at higher risk for postoperative pulmonary complications and mortality 5 , 6 , 7 , 8 . However, the risk for pediatric patients with SARS-CoV-2 infection undergoing surgery is not well understood, though several studies have sought to understand this question 9 , 10 , 11 , 12 . Our study was completed in the United States where vaccinations recently became available for children 5 years or older, leaving a portion of the pediatric population vulnerable to infection while approval for younger children is considered 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Saynhalath et al. found that respiratory adverse events in children with non‐severe SARS‐CoV‐2 infection were higher than in matched controls, irrespective of upper respiratory infection symptoms [ 14 ]. However, in that study, no child suffered complications such as postoperative pneumonia, acute respiratory distress syndrome or death.…”
Section: Discussionmentioning
confidence: 99%